Kemampuan Adaptasi Masyarakat Di Pulau-Pulau Kecil dalam Menghadapi Krisis Air (Studi Kasus: Pulau Buluh, Pulau Kelong dan Pulau Penyengat Provinsi Kepulauan Riau) - Putri, Chitra Widyasani Surya; Kusdariyanto, Irwan (Jurnal Sosial Ekonomi Pekerjaan Umum, 2014)
Vulnerability to the crisis of water resources occurs in the area of small islands which is considered vulnerable are as affectedby climate change. Indonesiahas 17.477 small islands (<2000 km2) which is in habited by20% of the total population of Indonesia, but the availability of water is not sufficient for the community to meet the increasing yearly demand. In 2014 the research activities carried out to measure the degree of adaptation to small islands in the face of these conditions. This study uses primary data with respondents heads of families who live on the Penyengat island, Buluh island, and the island Kelong. The research approach sedan index based on number of variables approaches a result of the vulnerability of the study area. The method used a composite index of the normalized data using the min-max values, weighting methods Iyengar and Sudharshanand is analyzed descriptively. The result of the analysis for the vulnerability index is 0.65 for Penyengat is land with a capacityof 0,131. Pulau Kelong has vulnerability index of 0.46with adaptive capacity of 0.170. Penyengat Island has a vulnerability index of 0.34 with adaptive capacity of 0,230. The conclusion shows that Penyengat island communities shave the worst adaptive capacity as compared to Kelong and Buluh Island. The study is expected to contribute to the government in the provision of infrastructure, especially water resources and good clean water suitable applied on small islands in Indonesia